Unexpected malignant uterine pathology: Incidence, characteristics and outcome in a large single-center series of hysterectomies for presumed benign uterine disease - Wagner, Philipp Georg; Kommoss, Felix; Wallwiener, Markus (Gynecologic oncology, 2019)
Objective - Hysterectomy is a frequently used therapeutic option for benign gynecological conditions. The purpose of this study was to investigate the incidence and characteristics of unforeseen malignant pathologies of the uterine corpus in a large population-based, single center cohort. - Methods - Patients who underwent hysterectomy for presumed benign conditions between 2003 and 2016 were identified. In cases of unexpected malignancies of the uterine corpus (UUM), available tissue samples were collected and a specialized gynecopathological review was performed. - Results - A total of 10,756 patients underwent hysterectomy for benign indications. After chart and gynecopathological review, 45/10,756 (0.42%) cases of unexpected uterine malignancies were confirmed. 33/45 (73.3%) were endometrial carcinomas (UEC) and 12/45 (26.7%) were uterine sarcomas (UUS). 27/33 (81.8%) UEC were FIGO IA, 5/33 (15.2%) FIGO IB and 1/33 (3%) FIGO stage II disease. Endometrioid and serous histotype were present in 31/33 (93.9%) and in 2/33 (6.1%) cases, respectively. 8/12 (66.7%) USS were early stage (FIGO IA or IB); only 3/12 (25.0%) were diagnosed at an advanced stage (≥FIGO II). Fatal outcome was observed in 1 patient diagnosed with UEC and 3 patients diagnosed with UUS. - Conclusion - Our study shows that diagnosis of UUM is rare (0.42%). The majority of UUM tend to be early stage, making preoperative diagnosis difficult. In case of UEC, patient outcome is generally favorable. Nevertheless, the appropriate surgical approach for hysterectomy for a benign indication should be chosen carefully, taking all preoperative findings into account. Patients should always be informed about the residual risk of UUM.
Gesehen am 29.01.2020